Bamidelê: por uma sociologia da informação étnico-racial na organização das mulheres negras da Paraíba - Silva, Leyde Klébia Rodrigues da (2014)
Information Science (IS) is field of knowledge which investigates about functioning of the processes of appropriation, organization, dissemination, access, use and democratization of information in all the fields of knowledge, sectors and members of society. Thus, this study analyzed how take place the processes of dissemination, and preservation of democratization Ethnic-racial information in the organization of black women (Bamidelê) in State of Paraíba/Brazil. Also it verified how Ethnicracial information is disseminated and democratized by the black women; and identified the actions used by Bamidelê Organization to preserve the cultural memory of the black population. For this, the methodological path was based on the qualitative approach of the research, descriptive and exploratory perspectives. The locus of Research was Bamidelê Organization, and the subjects of Research were black women coordinators of this Organization, beyond a group of women who were who is users of Organization (women who participate in any activity undertaken by the Organization) who also follow the Bamidele's Facebook Profile. The semistructured interviews and the Collective Subject Discourse (CSD) technique were the instruments used to data collection. The results inferred that appropriation, democratization, dissemination and preservation of Ethnic-racial information by Bamidelê Organization seeks to reach various sectors, as well as different audiences of society, ranging from more traditional sources of information to the most contemporary. The concluding remarks of the study show that the work begun by Bamidelê Organization significantly changed the Paraiba scenario, especially in the fight against racism and sexism. In this sense, the SI as field of knowledge plays an important role in the dissemination, democratization, and preservation Ethnic-racial information. The SI needs to open your theoretical and practical scope, because it may enable the emergence of new interdisciplinary spaces